Influence of the synthesis process on the features of Y2O3-stabilized ZrO2 powders obtained by the sol–gel method - Mamana, Nadia (2014)
Y2O3-stabilized ZrO2 (YSZ) powders have been prepared by the sol–gel method using different synthesis parameters. Specifically, zirconium n-propoxide was dissolved in propanol at pH 0.5 or 5 (provided by HNO3), with or without acetic acid in the hydrolysis medium. Subsequently, the YSZ powders obtained by gelation and drying of these solutions was characterized using scanning and transmission electron microscopies, X-ray diffractometry, and N2-adsorption. Compacts made from these YSZ powders which were then sintered were also analyzed. It was found that the pH of the hydrolysis medium has a notable influence on the microstructure, morphology, color, crystallinity, and sintering behavior process of these YSZ sol–gel powders. It was also found that the use of acetic acid also affects the YSZ powder features, and results in compacts with higher residual porosity after sintering. Finally, the compacts prepared from the YSZ powders obtained at pH 5 and without acetic acid exhibit the greatest sinterability